The Effect of Wall Pass Exercises and Exercises With Groups of 4 on Passing ResultsPS Undikma Mataram Football in 2024 - Fadli Zainuddin (Sinar Lima, 2024)
The focus of this research problem is that mistakes in passing often disrupt concentration and feeling nervous when competing. This results in passes not reaching friends, passing too fast, and passing carelessly so it doesn't match the target. So the 4-1 training model uses two touches and 4-1. The aim of this research is to determine the effect of wall pass training and exercise with groups of 4 on PS Undikma Mataram football passing results in 2024. The research methods used by researchers are the observation method, documentation method and action test method. The research design uses